THE PERFORMANCE OF THE JENDRAL AHMAD YANI ROAD IN CITY TENGGARONG - SAPUTRA, ANGGA HERY (KURVA S JURNAL MAHASISWA, 2020)
Jendral Ahmad Yani road in Tenggarong is a secondary arterial road that connects one primary and secondary area to another. The land use conditions found on the Jendral Ahmad Yani road are dominated by public buildings with general activities, namely settlements, shophouses and offices. Jendral Ahmad Yani road in Tenggarong belongs to the class III C road category. As the economy develops and the level of prosperity of the population increases, the level of travel increases, which occurs due to the need for transportation from the community, where people will always look for a faster, safer way and smooth. The increase in population and the amount of urbanization to urban areas will lead to a level of movement and density, so the need for transportation also increases. On this basis, a research was conducted on the performance of the Jendral Ahmad Yani road in Tenggarong. The Performance Analysis of the Jendral Ahmad Yani Road Section uses the Indonesian Road Capacity Manual (MKJI'1997), which is described based on Form UR-1 in the form of general and road Geometric Conditions, UR-2 in the form of advanced input data, namely Traffic and Composition Side barriers, UR-3 in the form of analysis of the speed of free flow of light vehicles, capacity and speed of light vehicles. In this Performance Analysis Study, the Jendral Ahmad Yani Road Section conducted a Khalid peak hour survey and the survey was conducted at 07.00-22.00. After calculating the existing data, Jendral Ahmad Yani is 1480.76 pcu / hour and the service level is at level C, which means the current zone is stable, the driver is limited to choosing speed.